Android Wireless Application Development - Darcey, Lauren; Conder, Sh ([S.l.] : Addison-Wesley Professional, 2012)
Android Wireless Application Development has earned a reputation as the most useful real-world guide to building robust, commercial-grade Android apps. Now, authors Lauren Darcey and Shane Conder have systematically revised and updated this guide for the latest Android SDK 4.0 . To accommodate their extensive new coverage, they$1 (Bve split the book into two volumes. Volume I focuses on Android essentials, including setting up your development environment, understanding the application lifecycle, designing effective user interfaces, developing for diverse devices, and optimizing your mobile app development process--from design through publishing. Every chapter has been thoroughly updated for the newest APIs, tools, utilities, and hardware. All sample code has been overhauled and tested on leading devices from multiple companies, and many new examples have been added. Drawing on decades of in-the-trenches experience as professional mobile developers, Darcey and Conder provide valuable new best practices--including powerful techniques for constructing more portable apps. This new edition contains full chapters on Android manifest files, content providers, effective app design, and testing; an all-new chapter on tackling compatibility issues; coverage of today$1 (Bs most valuable new Android tools and utilities; and even more exclusive tips and tricks. An indispensable resource for every Android development team member s
Keywords: Mobile computing; Application software; Android (Electronic resource); Development; Mobile apps; Wireless communication systems; Application software